Analisa Kualitas Sungai Siak Bagian Hulu - Husnil Fitri; Imam Suprayogi; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Siak River is one of the deepest rivers in Indonesia that is a national concern and it is a national strategic river. Currently, the Watershed of Siak especially in the upstream has included the critical watershed due to the decrease of river water discharge and increased activity along the river. In this research, identification of Pollutant Load Capacity of Upper Siak watershed with 9 segment and reducing pollutant load according to standard of class II. The polluted loads identified are BOD, COD and TSS parameters in the minimum discharge simulation. In the Siak basin the upstream reduction of the BOD pollutant load is 80%, COD 20% and TSS 20% to get the standard grade for class II. Result a pollution load capacity of Siak watershed after reduction for BOD, COD and TSS contaminant load according to standard of class for each class II is 3,548.01 kg / day, 308,407.15 kg / day and 149,138.67 kg / day.Key words : Siak River, Pollutan Load Capacity, WASP 7.3